A Rare Case of Primary Mediastinal Carcinoid Tumour Presenting with Hoarseness - Sadin, Zahra; Aghajanzadeh, Manouchehr; Jafanegad, Alirza; MD, Ali alive; Mosafaii, Omid; Safarpoure, Yasaman; Ayobi, Samman (Disease and Health: Research Developments Vol. 10, 2025)
Primary carcinoid tumours of the mediastinum are rare, particularly when arising from the posterior mediastinum and unrelated to the thymus. Mediastinal masses can cause challenges for thoracic surgeons. A unique case of a 48-year-old man was reported who presented with dyspnea, hoarseness, and weight loss due to a giant posterior mediastinal carcinoid tumour. Radiographic and CT findings confirmed a large mass compressing thoracic structures, originating from the left paravertebral region. Surgical resection via thoracotomy was performed successfully. Histopathological and immunohistochemical studies confirmed a neuroendocrine neoplasm (Grade II atypical carcinoid). The patient’s recovery after surgery went very well without complications. This case highlights the importance of early identification and surgical intervention in rare presentations of posterior mediastinal carcinoid tumours.